Risk stratification and assessment framework for international travel and border measures amidst the COVID-19 pandemic – A Malaysian perspective. Issue 47 (May 2022) - Omar, Khairul; Baha Raja, Dhesi; Abdul Taib, Nur Asheila; Rajaram, Nadia; Ahmed, Jinat; Arvinder-Singh, H.S.; Mokhtar, Siti Aisah; Teo, Alvin Kuo Jing; Amir, Lidwina Edwin; Chan, Michelle; Quek, Yee Theng; Ting, Choo-Yee
Abstract: Background: Guided by the best practices adapted from national and international bodies including the World Health Organization (WHO), the Centers for Disease Control (CDC), and the UK Joint Biosecurity Centre (JBC), this paper aims to develop and provide an empirical risk stratification and assessment framework for advancing the safe resumption of global travel during the COVID-19 pandemic. Method: Variables included in our model are categorized into four pillars: (i) incidence of cases, (ii) reliability of case data, (iii) vaccination, and (iv) variant surveillance. These measures are combined based on weights that reflect their corresponding importance in risk assessment within the context of the pandemic to calculate the risk score for each country. As a validation step, the outcome of the risk stratification from our model is compared against four countries. Results: Our model is found to have good agreement with these benchmarked risk designations for 27 out of the top 30 countries with the strongest travel ties to Malaysia (90%). Each factor within this model signifies its importance and can be adapted by governing bodies to address the changing needs of border control policies for the recommencement of international travel. Conclusion: In practice, the proposed model provides a turnkey solution for nations to manage transmission risk by enabling stakeholders to make informed, evidence-based decisions to minimize fluctuations of imported cases and serves as a structure to support the improvement, planning, and activation of public health control measures.